2009
DOI: 10.1089/ten.tea.2007.0394
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Copolymer Poly(Lactide-co-β-Malic Acid) with Extended Carboxyl Arms Offering Better Cell Affinity and Hemacompatibility for Blood Vessel Engineering

Abstract: Despite their increasing uses for cardiovascular and cerebrovascular tissue engineering, synthetic polymeric conduits still have their limitations in clinical applications, particularly in small vessels, mainly due to the thrombus formation. Seeding the synthetic scaffolds with endothelial cells (ECs) will potentially solve this problem, but this endothelialization approach demands synthetic materials with better hemacompatibility and cell affinity. To improve the currently used materials and screen for better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The results indicated that the peptide content of all the samples was similar and that the peptide densities on the surfaces were 1.3 pmol/ cm 2 approximately. 26,27 The wettability of the surfaces was not measured in this work, because the similarity of the peptide content and structure of the ALG-Pep modified surfaces would result in similar contact angles. The roughness of the surface was characterized by the value of root mean square roughness (RMS, Table I).…”
Section: Characterization Of the Alg-pep Modified Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the peptide content of all the samples was similar and that the peptide densities on the surfaces were 1.3 pmol/ cm 2 approximately. 26,27 The wettability of the surfaces was not measured in this work, because the similarity of the peptide content and structure of the ALG-Pep modified surfaces would result in similar contact angles. The roughness of the surface was characterized by the value of root mean square roughness (RMS, Table I).…”
Section: Characterization Of the Alg-pep Modified Surfacesmentioning
confidence: 99%
“…This indicated that the variation in surface morphology would not affect the results of latter studies. 26,27 The wettability of the surfaces was not measured in this work, because the similarity of the peptide content and structure of the ALG-Pep modified surfaces would result in similar contact angles. 28…”
Section: Characterization Of the Alg-pep Modified Surfacesmentioning
confidence: 99%
“…40,41 Large vascular conduits appear to be a more feasible target, and preclinical and early clinical studies indicate successful single and combination cell seeding of synthetic vascular grafts. 40,41 An alternative strategy includes mobilization of endogenous progenitors onto grafts and stents in vivo. This has been achieved using CD34 antibodies (EPC stent) and has undergone successful human safety trials.…”
Section: Kumar and Caplice Potential Of Adult Vascular Progenitor Celmentioning
confidence: 99%
“…Under the majority of common catalytic hydrogenolysis conditions including 1, 3, or 6 atm of hydrogen, a range of catalysts (Pd/C, Pd(OH) 2 /C, or PdCl 2 /Pd black) and a variety of solvents (ethyl acetate, methylene chloride, acetic acid, or THF), no deprotection was observed. [21,23,24,28,29] Only in DMF was the deprotection viable. [30] We hypothesize that DMF promotes the hydrogenolysis by optimal solvation of both the relatively non-polar benzyl-protected polymer and the considerably more polar poly(hydroxyl) product and/or by providing the minimum activation enthalpy between the benzyl-protected polymers and the more polar transition state.…”
Section: Synthesismentioning
confidence: 99%